MoSi2/Al2O3/Feldspar Composites for Injection‐Molded Ceramic Heating Elements. Issue 9 (21st September 2021) - Wick-Joliat, René; Mauchle, Stéphane; Kontic, Roman; Ehrat, Sandro; Hocker, Thomas; Penner, Dirk
Abstract : The cover illustrates the sintering of MoSi2 /Al2 O3 /Feldspar heating elements fabricated by injection molding, thus allowing more complex geometries and more economical heating element production, see the article number 2100517 by Dirk Penner and co‐workers. Different binder systems are investigated and heating elements of various shapes as shown in the illustration are produced and tested. (Cover design: René Wick‐Joliat)